Qualitative and quantitative phytochemical analysis, antimicrobial potential and antioxidant activity of selected herbs Piper betle and Persicaria odorata leaf extracts - Basit, Muhammad Abdul; Abdul Kadir, Arifah; Loh, Teck Chwen; Salleh, Annas; Kaka, Ubedullah; Idris, Sherifat Banke; Farooq, Abdul Asim; Javid, Muhammad Arshad; Murtaza, Saeed (Asian Journal of Agriculture and Biology, 2023)
Plants, their extracts, and plant essential oils are considered prominent sources of new therapeutic substances. Nowadays, medicinal plants like herbs attain the keen interest of consumers and researchers. The present study evaluated Piper betle (P. betle) and Persicaria odorata (P. odorata) leaf extracts for qualitative and quantitative phytochemical screening. The phytochemical analysis of P. betle and P. odorata leaf extracts presented the occurrence of tannins, flavonoids, saponins, phenols, glycosides, and volatile oils. The higher total phenolic content and total tannins were quantified from P. betle methanolic leaf extract. Additionally, it showed increased antioxidant activity compared to P. odorata leaf extracts. The in vitro antibacterial potential of both herbs was estimated against Salmonella enterica, Pseudomonas aeruginosa, Escherichia coli, Bacillus subtilis, Staphylococcus aureus, Candida albicans, and Aspergillus brasiliensis. The methanolic leaf extract of Piper betle showed antibacterial and antifungal activity against these selected strains.